Magi Is Associated with the Par Complex and Functions Antagonistically with Bazooka to Regulate the Apical Polarity Complex. - Padash Barmchi, M.; Samarasekera, G.; Gilbert, M.; Auld, V.J.; Zhang, B. (PLoS ONE, 2016)
The mammalian MAGI proteins play important roles in the maintenance of adherens and tight junctions. The MAGI family of proteins contains modular domains such as WW and PDZ domains necessary for scaffolding of membrane receptors and intracellular signaling components. Loss of MAGI leads to reduced junction stability while overexpression of MAGI can lead to increased adhesion and stabilization of epithelial morphology. However, how Magi regulates junction assembly in epithelia is largely unknown. We investigated the single Drosophila homologue of Magi to study the in vivo role of Magi in epithelial development. Magi is localized at the adherens junction and forms a complex with the polarity proteins, Par3/Bazooka and aPKC. We generated a Magi null mutant and found that Magi null mutants were viable with no detectable morphological defects even though the Magi protein is highly conserved with vertebrate Magi homologues. However, overexpression of Magi resulted in the displacement of Baz/Par3 and aPKC and lead to an increase in the level of PIP3. Interestingly, we found that Magi and Baz functioned in an antagonistic manner to regulate the localization of the apical polarity complex. Maintaining the balance between the level of Magi and Baz is an important determinant of the levels and localization of apical polarity complex.